Konsepsual Model Bagi Mengukur Kualiti Perkhidmatan Perpustakaan Akademik (Sains Humanika, 2018)
The Ninth Malaysia Plan (RMK-9) is the second phase of a national mission to achieve Vision 2020. The Eleventh Malaysia Plan (RMK-11), 2016-2020, is the latest five-year development plan towards realizing Vision 2020. One of the core the main is to increase knowledge and innovation and nurture first class mentality among Malaysians. Higher Education Institutions (HEIs) have a big responsibility to realize this vision. Thus, learning assessment instruments analyzed by Asif and Searcy should be improved to make it more comprehensive and relevant to current needs. For this purpose, an empirical study was conducted in which the data accessed across multiple groups of library user’s background from 5 HEIs (private and public) in the north of Peninsular Malaysia. This study involved 381 respondents as the sample. The reliability tests through 3 criteria displayed the internal consistencies of the seven factors were satisfactorily (α=0.70): Coefficient Alpha (CA), Corrected Item-Total Correlation (CITC) and Alpha if Item Deleted (IID). It shows all constructs have to comply with three criteria, namely CA, CITC and the IID. Meanwhile for the content validity views of experts was conducted. All comments have been improved before final questionnaire distributed. As a conclusion, the result indicated that the model was highly goodness fit for measuring library services, and all dimensional constructs supported the proposed theoretical model.
Keywords: Quality model; library services; Higher Education Institution (HEI); library performance.